A(s) metáfora(s) de leitura no texto de prefácio "Bom de Ouvido" de Ana Maria Machado - Canalle, Grazielli Alves Almeida (2016)
This research analyzes the reading metaphors produced in the discourse of the introduction text 'Bom de Ouvido' by Ana Maria Machado, about the book "Comédias para se Ler na Escola" by Luis Fernando Verissimo. Our research is based on theoretical studies in Discourse Analysis, whose basic authors are Pêcheux and Orlandi. The main question is: what metaphor is in the discourse of this introduction text? To think about this question, we selected two discursive sequences of reference and some cuts that are affiliated to them. From these discursive sequences, we understand that some changing in meanings occurs, thus, two reading metaphors are produced: reading like dating and reading like sport. The introduction place shows itself as an exaltation place and serves as a guide for the reader, which characterizes it as a pedagogical discourse. From the metaphor reflections as the basis for presentation objects to subject proposed by Pêcheux, we conclude that the metaphor reads both the text and the reader, it is located in this between, this is, and the metaphor does the mediation between the reader and the book. The school, in turn, is configured as a condition of appearance of these kinds of metaphors, as a significant space that produces and reproduces the modern subject.